UJI MODEL HIDROLIKA KINERJA PEMECAH GELOMBANG APUNG BETON DENGAN KONFIGURASI GANDA - Irham Adrie Hakiki; Leo Eliasta Sembiring (JURNAL TEKNIK HIDRAULIK, 2020)
Development of floating breakwater technology is increasing along with the rising interest of floating infrastructure. Different kind of materials and shapes were researched for optimizing the performance of floating breakwater. In comparison of structure with a similar dimension, the more rigid one gave a better performance. Large and rigid structure are possible to construct with the usage of concrete. However, when there is a limit to the structure dimension, whether it is caused by construction or transportation method, the alternatives for improving performance are needed. This research proposed a double configuration setup to cope with the said limitation. The breakwater performance is tested with physical model in laboratory by comparing performance of single pontoon with double pontoon for various structure spacing. Pontoon size are 1.2 m in length, 0.3 m in width, and 0.15 m in height and tested with many combinations of irregular waves. For double configurations model, the spacing of 30 cm, 60 cm, and 90 cm are used. Based on tested result, there are improvement up to 20% by using the double configuration. The improvement determined by ratio of structure spacing with wavelength. Larger ratio resulted a better performance in condition where the spacing did not exceed 0,65 length of wavelength.